Poéticas corporais: o corpo no ambiente natural: uma proposta contemporânea em arte visual - Tura, Paula Ferreira (2014)
This research, through the visual arts sacralizes the contact of the human body with the natural environment. The author who is an artist-researcher has chosen the Contemporary Art as a language to her proposals. The dissertation was written in One Chapter composed as: interventions developed by the researcher with photos and descriptions followed by an artist of reference with images of it´s work and an analysis of the art work proposed by the researcher with concepts and discussion of arguments. To each posture of Contemporary Art there is a range of different art pieces to be viewed: Body Art there is a body painting and imprinting, and cast´s mold of body parts; Performance Art-there are registration of the shadows produced by the body during an yoga practice and the projection of the shadow of a tree leave on top of a body and the match of the body with a tree and a ruin of a building; Arte Povera there is a branch painted in red and the construction of a feminine body with sand and cloth; Land Art there is a construction of little cloth trees, the drawings on the beach sand, a collective work to make rocks softer, the creation of colorful and sand paths and the interventions with ink on sand sculptures found at the beach. The body, main object of this work, feels and become visible the marks of restlessness that carry about the social imposed patterns of behavior and esthetics and the relation with the natural environment. Carry itself the memories of choices made and paths coursed. The art proposals here included express what the speech misses, express the pains of the reflexive path coursed, the listening, the feeling, the contemplation, the process of waiting.